Effect of therapeutic exercise on the balance of patients with progressive supranuclear palsy: A pilot study - Matsuda, Naomi; Takamatsu, Yasuyuki; Aiba, Ikuko (Frontiers in Neurology, 2022)
Background: Progressive supranuclear palsy (PSP) is a parkinsonian-like progressive neurodegenerative syndrome. Key clinical features include ocular motor dysfunction, postural instability, and cognitive dysfunction. Maintaining and improving balance function and gait function are very important for patients with PSP with severe postural dysfunction and repeated falls. In addition, patients with PSP have a poor response to pharmacological treatment; hence, rehabilitation is a key approach in dealing with this syndrome. However, no conclusion on the beneficial effects of rehabilitation for patients with PSP have been established in the literature. Objectives: The effectiveness of multiple therapeutic exercise program with probable or possible PSP according to the Movement Disorder Society criteria for the clinical diagnosis of PSP was validated. Methods: Participants underwent multiple therapeutic exercise program customized for each participant, including resistance training, balance training, and walking exercises that were performed for 60–80 minutes a day, 5 days a week for 4 weeks. The outcomes measured were as follows: pull test, Berg Balance Scale (BBS), timed up and go test (TUG), and gait speed test. Results: A total of 117 patients with PSP were enrolled and the analysis was performed on 20 patients with probable PSP. Four-week rehabilitation significantly improved pull test (p = 0.034) and BBS scores (p = 0.001). There were no significant differences between TUG (p = 0.502) and gait speed (p = 0.813). Conclusion: The multiple therapeutic exercise program had beneficial effects on balance performance in patients with PSP in 4 weeks and could be an essential element in their rehabilitation. Although this pilot study was conducted without a control group, it provided valuable information for future prospective randomized controlled trials.